THE NATIVE IDENTIFICATION FRIEND-FOE OF BRAZIL: QUESTIONS AND REPLIES DOI 10.5028/jatm.2010.02038710 - Eric Julius Wurts (Journal of Aerospace Technology and Management, 2011)
This paper discusses the System of Identification Friend-Foe (IFF) with genuinely national technology, including Mode 4 with native encryption. Actual fratricides are illustrated and the Brazilian processes to reduce them are shown. Technical aspects of IFF systems in use by the North Atlantic Treaty Organization (NATO), are reviewed and updated based on the standards of NATO Standardization Agreement (STANAG 4193). The analysis shows that the current stage of development of the industry of National Defense, coupled with its ability to integrate with the technological centers of the Armed Forces, as well as the availability of budget for research and development, resulting from the National Defense Policy, are factors for the success of the project. Also, it exposes the importance of combining air defense and air traffic control in Brazil as a determinant factor for the success of the task. The solution should be based on maintaining the standards laid down in STANAG 4193 technical characteristics of interrogators and transponders of IFF Mark XII, keeping the processes of interrogation and “response”. Results indicate the need of providing grants to study the incorporation of Mode 5 and Mode S, in a second step